Genetic Analysis of Gv1, a Gene Controlling Transcription of Endogenous Murine Polytropic Proviruses - Oliver, Peter L. (American Society for Microbiology, 1999)
Gv1 is a genetic locus that coordinately regulates the expression of multiple murine leukemia virus-related endogenous proviral sequences. A quantitative nuclease protection assay for typing Gv1 inheritance has been developed. Use of this assay demonstrates that Gv1 controls transcription of polytropic but not of modified polytropic endogenous proviruses. A combination of genetic techniques were used to map Gv1; these analyses demonstrate that Gv1 lies approximately 37 centimorgans from the centromeric end of mouse chromosome 13.